The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1136/jim-2020-001650
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Progression-Free Survival of Patients with Metastatic Melanoma or Renal Cell Carcinoma following High-Dose Interleukin-2

Abstract: High-dose interleukin-2 (HD IL-2) was approved in the 1990s after demonstrating durable complete responses (CRs) in some patients with metastatic melanoma (mM) and metastatic renal cell carcinoma (mRCC). Patients who achieve this level of disease control have also demonstrated improved survival compared with patients who progress, but limited data are available describing the long-term course. The aim of this study was to better characterize long-term survival following successful HD IL-2 treatment in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…80 81 In subsequent and contemporary follow-up of patients undergoing this treatment, decadelong disease-free and treatment-free survivors are reported. [82][83][84][85][86][87] A recent report describes the clinical benefit (complete response+partial response+stable disease-CR+PR+SD) and OS for patients treated with IL-2, according to clinical risk groups. 64 For patients treated with IL-2 only, the favorable risk group had a clinical benefit rate of 76% and a median OS of greater than 5 years.…”
Section: Sites Of Metastatic Disease: Special Consideration Of Bone A...mentioning
confidence: 99%
See 2 more Smart Citations
“…80 81 In subsequent and contemporary follow-up of patients undergoing this treatment, decadelong disease-free and treatment-free survivors are reported. [82][83][84][85][86][87] A recent report describes the clinical benefit (complete response+partial response+stable disease-CR+PR+SD) and OS for patients treated with IL-2, according to clinical risk groups. 64 For patients treated with IL-2 only, the favorable risk group had a clinical benefit rate of 76% and a median OS of greater than 5 years.…”
Section: Sites Of Metastatic Disease: Special Consideration Of Bone A...mentioning
confidence: 99%
“…IL-2 therapy, a T-cell growth factor, is the early immunotherapy which has achieved significant numbers of patients with metastatic RCC having decades-long disease-free survival, possibly cures, following treatment, which is almost unique among advanced adult solid tumors. [82][83][84][85][86][87] These patients include subjects in both favorable and intermediate risk categories and those with clinical benefit after treatment (CR+PR+SD) but particularly CR+PR. 87 Therefore, the goal of all new clinical trials and particularly combination regimens should be to enhance the percentage of patients who achieve durable response and prolonged survival, preferably off-therapy.…”
Section: Goal Of Management Of Metastatic Rccmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some previous experiences regarding the discontinuation of immunotherapy in melanoma. Specifically, high-dose interleukin-2 and the anti- CTLA-4 agent ipilimumab were associated with complete and durable responses, albeit limited in number, that occurred within only a few months of therapy [ 35 , 36 ]. However, preliminary data from controlled clinical trials do not point in the same direction.…”
Section: Discussionmentioning
confidence: 99%
“…Early trials of HD IL-2 showed that this treatment elicited durable responses in 10-15% of patients with melanoma and in 15-25% of those with RCC ( 1 3 ). Contemporary studies continue to report durable responses and survival rates, mainly in patients obtaining CR ( 38 40 ). Encouraged by these recent reports, the interest in IL-2 as a combination or sequential therapy to further improve objective response remains high ( 20 , 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%